The Changing Face of Lung Cancer: Survivor Perspectives on Patient Engagement - Margaret I Fitch (Elsevier, 2019)
Objective: Advances in the diagnosis and treatment of lung cancer have resulted in an increasing number of individuals living longer following their diagnosis. No longer is lung cancer the "death sentence" it once was. This initiative was designed to document the current experiences of lung cancer patients and explore the potential for patient engagement. Methods: Three avenues of investigation were undertaken: a literature review regarding lung cancer and patient engagement, an environmental scan of lung organizations and cancer societies regarding their approaches to lung cancer patient and family engagement, and in-depth interviews with lung cancer survivors and family members about their experiences and perspectives about patient engagement. Information was collated and major themes identified. Results: Evidence about the experience of lung cancer patients illustrates their needs are complex and dynamic. It also presents a clear picture of unmet physical, psychosocial, and spiritual needs. In particular, stigma is a significant issue for those diagnosed with lung cancer. Information, support, and communication play important roles in helping patients cope but access to resources remains challenging. Patients and family members expressed interest in becoming engaged in advocacy to improve care. Conclusions: The changing face of lung cancer creates the potential for lung cancer survivors to become engaged not only in participating in their own care but also become more involved in peer support and advocacy than lung cancer patients have been able to do in the past.